Evaluation of DVB-T2 Digital TV Propagation Performance in the Bali Broadcast Area - Pradnyana, I Made; Widyantara, I Made Oka; Pramaita, Nyoman (ASTONJADRO, 2023)
The development of terrestrial television broadcasting technology in the world today is switching from analog broadcasting systems to digital broadcasting systems. Analog Switch Off (ASO) is the period when analog broadcasts are stopped and replaced with digital broadcasts. Through the jargon "Clean Picture, Clear Sound, Advanced Technology" people will feel better quality than analog TV. In the era of digital broadcasting, TV viewers not only watch broadcast programs but can also get additional facilities such as EPG (Electronic Program Guide) to find out the programs that have been and will be aired later. With digital broadcasting, there is the ability to provide interactive services where viewers can directly rate the sound of broadcast programs in addition to the presence of features that can be utilized, such as features related to disaster information. In this study, an evaluation of the performance of DVB-T2 Digital TV propaganda will be carried out in the Bali service area. The quality of digital TV broadcasts in the Bali broadcast area is influenced by signal propagation which is parameterized by parameters C / N (or S / N), Modulation Error Rate (MER), Bit Error Rate (BER) by measuring at the test point or location of the test point/test measurement which is the outermost limit of the service area under the Minister of Communication and Information no 23 / PER / M.KOMINFO / 11/2011. So this research can be produced a map of the quality of broadcasting services in Bali which can be used as an indicator to avoid Bali from blank spot areas that can be recommended for Digital TV operators in Bali for repeater installation planning.